231k views
2 votes
6(−2g−1)=−(13g+2) Solve for g

User Cyker
by
5.7k points

2 Answers

1 vote

Answer:

g=4

Explanation:

User Hood
by
5.2k points
4 votes

Answer:

The solution is g = 4

Explanation:

* 6(-2g - 1) = -(13g + 2)

- We need to solve it to find the value of g

- Let us simplify each side and then solve the equation

∵ 6(-2g - 1) = (6)(-2g) - (6)(1)

∴ 6(-2g - 1) = -12g - 6

∴ The simplify of 6(-2g - 1) is -12g - 6 ⇒ (1)

∵ -(13g + 2) = -13g - 2

∴ The simplify of -(13g + 2) is -13g - 2 ⇒ (2)

- Equate (1) and (2)

-12g - 6 = -13g - 2

- Add 13g to both sides

∴ g - 6 = - 2

- Add 6 to both sides

g = 4

* The solution is g = 4

User Raduan Santos
by
6.6k points